Effect of Premna pubescens Ethanol Extract on Erythrocyte Count and Kidney Histology in Rattus norvegicus L - Silaen, Srinatalia (Politeknik Negeri Batam, 2024)
Premna pubescens (wild leaves) has a rich history of traditional medicinal use, including as an anti-inflammatory, antioxidant, and anticancer agent. This study aimed to investigate the potential therapeutic effects of the ethanol extract of Premna pubescens leaves on erythrocyte count and kidney histology in Rattus norvegicus L. Twenty-four male Wistar rats were divided into four groups: control, ethanol extract of wild leaves, Sheep Red Blood Cell (SRBC) antigen, and combined ethanol extract with SRBC. The experiment involved administering wild leaf ethanol extract at 250 mg/kg BW for 30 days, followed by SRBC injection on days 8 and 15. Erythrocyte counts were measured, and kidney histological changes were observed.The results showed a significant increase in erythrocyte count in the A1 (7.42 ± 0.35 million cells/μl) and A3 groups (7.77 ± 0.23 million cells/μl) compared to the control group (7.05 ± 1.07 million cells/μl) and SRBC-treated rats (6.61 ± 0.18 million cells/μl). Histological analysis of the kidneys revealed clearer glomeruli and tubules, with reduced signs of inflammation and bleeding compared to the SRBC-treated group. These findings suggest that Premna pubescens extract has potential therapeutic effects on erythrocyte count and renal tissue, likely due to its antioxidant and anti-inflammatory properties. In conclusion, the ethanol extract of Premna pubescens shows promise in positively affecting erythrocyte count and mitigating kidney damage, demonstrating its potential as a therapeutic agent.